Synthesis and characterization of a new energetic metal–organic framework for use in potential propellant compositions. Issue 15 (9th July 2020) - Wu, Shuo; Li, Min; Yang, Zhengyi; Xia, Zhengqiang; Liu, Bin; Yang, Qi; Wei, Qing; Xie, Gang; Chen, Sanping; Gao, Shengli; Lu, Jack Y.
Abstract : A new green energetic metal–organic framework has potential application prospects in the fields of greener propellants and multi-dimensional magnetic materials. Abstract : Based on a nitrogen-rich Y-shape energetic ligand, tris(5-aminotetrazole)triazine (H3 TATT), a new green solvent-free energetic metal–organic framework (EMOF) [Co(HTATT)] n, has been synthesized under hydrothermal conditions. X-ray single crystal structure analysis shows that [Co(HTATT)] n has a 3D framework structure with building units [Co1-(μ4 ′-HTATT)-Co1]. The thermal decomposition behavior, the kinetic parameters of the exothermic process, the calculated detonation properties and sensitivities to impact and friction stimuli of [Co(HTATT)] n were investigated. Using differential scanning calorimetry, [Co(HTATT)] n was explored as a combustion promoter to accelerate the thermal decomposition of ammonium perchlorate (AP). Experimental results indicated that [Co(HTATT)] n possesses potential application prospects in the field of greener propellants. Magnetic measurements performed on [Co(HTATT)] n with the tetrazolyl-bridged Co(ii ) EMOF structure display spin-glass behavior with the coexistence of spin-canting ordering below 4.0 K.